MENINGKATKAN NILAI KEBHINEKAAN GLOBAL MELALUI BAHAN AJAR BERBASIS BUDAYA LOKAL DI KELAS TIGA SD BALI BILINGUAL SCHOOL - Purnami, Ni Made Ayu; Nurhidayati, Wahyu (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study examines how third-grade students at Bali Bilingual School can improve global diversity values ​​by using local culture-based teaching materials. This study used a qualitative approach to collect data from classroom observations, interviews with teachers, and analysis of curriculum documents. Students who received local culture-based lessons had a better understanding of cultural diversity and were more tolerant. These teaching materials enriched students' insights into local culture and taught them to appreciate diversity around the world because they combined the various diversities that exist in Indonesia. According to this study, local culture-based education is an effective tool for building global diversity from an early age. The teaching materials themed on increasing the value of global diversity through local culture-based teaching materials in the third grade of Bali Bilingual School Elementary School have an optimal level of suitability. The evaluation results showed that students' post-test scores increased significantly. The average student score was 65% at the pre-test stage. After the local culture-based teaching materials and interactive learning methods were implemented, the average student score increased to 90% at the post-test stage. This 25% increase shows how effective the teaching materials are in increasing students' understanding and appreciation of global diversity.